Tropomyosin movement is described by a quantitative high-resolution model of X-ray diffraction of contracting muscle - Koubassova, Natalia A. (2017)
Contraction of skeletal and cardiac muscle is controlled by Ca2+ ions via regulatory proteins, troponin (Tn) and tropomyosin (Tpm) associated with the thin actin filaments in sarcomeres. In the absence of Ca2+, Tn-C binds actin and shifts the Tpm strand to a position where it blocks myosin binding to actin, keeping muscle relaxed. According to the three-state model (McKillop and Geeves Biophys J 65:693–701, 1993), upon Ca2+ binding to Tn, Tpm rotates about the filament axis to a ‘closed state’ where some myosin heads can bind actin. Upon strong binding of myosin heads to actin, Tpm rotates further to an ‘open’ position where neighboring actin monomers also become available for myosin binding. Azimuthal Tpm movement in contracting muscle is detected by low-angle X-ray diffraction. Here we used high-resolution models of actin-Tpm filaments based on recent cryo-EM data for calculating changes in the intensities of X-ray diffraction reflections of muscle upon transitions between different states of the regulatory system. Calculated intensities of actin layer lines provide a much-improved fit to the experimental data obtained from rabbit muscle fibers in relaxed and rigor states than previous lower-resolution models. We show that the intensity of the second actin layer line at reciprocal radii from 0.15 to 0.3 nm−1 quantitatively reports the transition between different states of the regulatory system independently of the number of myosin heads bound to actin.